2013
DOI: 10.1111/cbdd.12191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Leishmanicidal and Trypanocidal Activities of Aliphatic Diamine Derivatives

Abstract: Leishmanicidal and trypanocidal activity of seventeen lipophilic diamines was evaluated in vitro against Leishmania braziliensis, L. chagasi, and Trypanosoma cruzi. Twelve compounds presented anti-Leishmania and six showed anti-T. cruzi amastigote activity. Compound 14 (N-tetradecyl-1,4-butanediamine) was the most active against both L. braziliensis (IC50  = 2.6 μm) and L. chagasi (IC50  = 3.0 μm) which showed a selectivity index (SI) >100. N-decyl-1,6-hexanediamine (compound 9) presented an IC50  = 1.6 μm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The first generation of these compounds consisted of symmetrically or nonterminally alkylated polyamine analogs [187]. Substituted polyaminebased derivatives have also been identified, including diamines and imidazole-containing drugs like triclabendazole (comp 10), which showed a multisite mode of action in the parasite [188][189][190] (Figure 9). Several drug screenings have been carried out to identify novel polyamine uptake inhibitors against T. cruzi [190].…”
Section: Inhibitors Of Polyamine Uptakementioning
confidence: 99%
“…The first generation of these compounds consisted of symmetrically or nonterminally alkylated polyamine analogs [187]. Substituted polyaminebased derivatives have also been identified, including diamines and imidazole-containing drugs like triclabendazole (comp 10), which showed a multisite mode of action in the parasite [188][189][190] (Figure 9). Several drug screenings have been carried out to identify novel polyamine uptake inhibitors against T. cruzi [190].…”
Section: Inhibitors Of Polyamine Uptakementioning
confidence: 99%
“… 12 , 13 Interestingly, the development of ferroquine, an analogue of chloroquine with an Fc group in the lateral chain, showed particularly good in vitro and in vivo activity against chloroquine-resistant malaria parasite strains. 14 Considering the success of this approach and because alkyl diamines had been recently proposed as leading molecules for the development of new antiparasitic drugs, 15 our team decided to investigate the activity of novel Fc diamine hydrochlorides against T. cruzi and T. brucei. 16 The results revealed that the Fc derivatives were toxic either to T. cruzi and T. brucei , but not toxic to HepG2 cells, a model of mammalian cells.…”
Section: Introductionmentioning
confidence: 99%